Modelling Quality of Service - Rahayu Tri Utami; Reza Ronaldo; Eva Rahmawati (Jurnal Mantik, 2022)
This research was conducted because of the increasing number of customer complaints at the Mobile Store in Ukui, this shows that customer satisfaction at the Mobile Store in Ukui is low. Therefore, the research objective is to analyze the effect of physical evidence, reliability, responsiveness, assurance and empathy on customer satisfaction. The research sample is 86 respondents. By using purposive sampling method is a sampling technique that uses certain criteria. This study uses multiple linear regression analysis tools. The results of this study indicate that physical evidence, responsiveness, and empathy have a significant effect on customer satisfaction and assurance while empathy has not effect on customer satisfaction.